PENGARUH INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
The issue of inflation is a very important indicator in terms of maintaining economic stability. It can be said that inflation is one of the important factors influencing the economic growth of a country. Economic growth is a goal to be achieved by every country. Keynesian theory states that in the short run, national output and employment are determined primarily by aggregate demand. When the inflation rate increases, which is followed by an increase in interest rates, investors will borrow capital from banks to expand their investment range, which in turn will affect economic growth. This study aims to analyze the effect of inflation on economic growth in Indonesia using the OLS model. This study uses a quantitative approach method. Data collection method using secondary data. The data analysis method used in this research is simple linear regression analysis using the Ordinary Least Square (OLS) method with calculations performed through the SPSS program. Based on the results of the tests that have been carried out, it is found that inflation has a negative effect on economic growth